Bongal Site of Central Tapanuli: Early Traces of the Spread of Christianity as a Learning Resource for History Subject in High Schools - Rosmaida Sinaga; Ichwan Azhari; Lister Eva Simangunsong; Pulung Sumantri (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to present the findings from the Bongal Site as an essential learning resource for the History subject in Senior High Schools, particularly in exploring the dynamics of cultural interaction and the spread of religion in the Indonesian archipelago during ancient times. Methodology: This research employs a qualitative methodology, integrating historical and archaeological approaches. The historical approach is used to reconstruct the process of Christianity’s arrival on the west coast of Sumatra. At the same time, archaeological data are supported by an extensive literature review and field observations. Main Findings: The findings reveal that the spread of early Christianity to Sumatra, though still debated among historians, is evidenced by written sources indicating the presence of the Nestorian Church in the Fansur (Barus) region. Archaeological excavations at the Bongal Site uncovered various artifacts such as rings engraved with crosses, Roman beads, carved stones with Christian symbols, and Byzantine liturgical spoons that support this narrative. Novelty/Originality of this study: The originality of this study lies in the identification and comparative analysis of artifacts that bear significant resemblance to early Roman and Byzantine Christian objects. These findings not only offer new insights into the early presence of Christianity on Sumatra’s west coast but also support the use of the Bongal Site as a contextual and meaningful historical learning resource in secondary education.